Factors associated with knowledge of the disease in people with type 2 diabetes mellitus - Amaral, Verônica Rabelo Santana; Ribeiro, Ícaro José Santos; Rocha, Roseanne Montargil (Investigación y Educación en Enfermería, 2021)
Objective. To identify factors associated with the level of knowledge of the disease in people with type 2 Diabetes. Methods. A cross-sectional study carried out with 412 people with diabetes registered in the Primary Health Care network of a Brazil Northeast municipality. For data collection, we used a questionnaire with sociodemographic and clinical variables and to identify the level of knowledge, we used the Diabetes Knowledge Questionnaire. Results. Insufficient knowledge prevailed in 54.7% of the participants, associated in significant bivariate analysis (p<0.05) with the sociodemographic variables: age (≥ 60 years old), marital status (without a partner), education (up to complete / incomplete elementary school), family income (≤ 1 minimum wage). For clinical variables, the level of insufficient knowledge was significantly associated with not participating in an educational group, not using insulin, and not practicing physical activity. In logistic regression, we observed that the factors that increase the risk for insufficient knowledge were: never having participated in an educational group (OR=2.0), age ≥ 60 years old (OR=2.2), illiterate and primary education (OR=8.3) and income less than or equal to 1 minimum wage (OR = 2.4). Conclusion. The level of knowledge of people with type 2 diabetes mellitus about their disease is insufficient, with socioeconomic and educational characteristics being the factors that increase the odds of having this level of knowledge.